2020
DOI: 10.3390/cancers12102745
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in 472 Human Cerebrospinal Fluid: Changes in Extracellular Vesicle Concentration and miR-21 Expression as a Biomarker for Leptomeningeal Metastasis

Abstract: Leptomeningeal metastasis (LM) has a poor prognosis and is difficult to diagnose and predict the response of treatment. In this study, we suggested that the monitoring of changes in the concentration of extracellular vesicles in cerebrospinal fluid could help diagnose or predict outcomes for LM. We measured nanoparticles in 472 human cerebrospinal fluid (CSF) from patients including LM with both Dynamic Light Scattering (DLS) and Nanoparticle Tracking Analysis (NTA) after two-step centrifugations. NTA revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Two challenges in characterizing exosomes in the context of neurodegenerative diseases are the limited sample volume of CSF and the abundance of nanoparticles in CSF that are similar to exosomes in size and density, [ 270 ] contaminate isolated exosome samples, and cannot be distinguished by NTA. [ 271 ] Novel methods have been developed to address these challenges.…”
Section: Exosome Characterizationmentioning
confidence: 99%
“…Two challenges in characterizing exosomes in the context of neurodegenerative diseases are the limited sample volume of CSF and the abundance of nanoparticles in CSF that are similar to exosomes in size and density, [ 270 ] contaminate isolated exosome samples, and cannot be distinguished by NTA. [ 271 ] Novel methods have been developed to address these challenges.…”
Section: Exosome Characterizationmentioning
confidence: 99%
“…GBM-patient serum samples (36). Similarly, miR-21 was consistently found to be enriched in EVs isolated from blood samples of patients affected by GBM (36, 74) as well as from the CSF of patients with leptomeningeal metastasis (75). Interestingly, miR-21was also found to be enriched in EVs isolated from brains of murine models of traumatic brain injury where the brain trauma was mimicked with a craniotomy followed by a controlled damage of the dura (76).…”
Section: Accepted Articlementioning
confidence: 95%
“…MiR-21 may even be useful in rare cancers with few available biomarkers. In leptomeningeal metastasis (LM) patients, miR-21 expression was monitored using EVs extracted from cerebrospinal fluid (CSF) and found that aberrant miR-21 expression correlated with patient survival [ 112 , 113 , 114 ].…”
Section: Microrna-21 As a Biomarker In Cancermentioning
confidence: 99%
“…Current evidence demonstrates that miR-21 exerts immense influence on cancer progression, including strong effects on cancer cell proliferation, stemness, apoptosis, and chemoresistance. In addition, circulating miR-21 can not only be used as a diagnostic tool but also as a targetable functional component of systemic intercellular communication in cancers such as GBM and LM [ 108 , 112 ]. Although the ability to predict interactions and create therapeutic avenues for inhibiting miR-21 has advanced significantly in the past decade, complications related to cancer heterogeneity and the intricate web of the microenvironment itself have become increasingly apparent.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%